2012
DOI: 10.1175/jpo-d-11-0159.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Geostrophic Circulation of the Mediterranean Sea Derived from Drifter and Satellite Altimeter Data

Abstract: Drifter observations and satellite-derived sea surface height data are used to quantitatively study the surface geostrophic circulation of the entire Mediterranean Sea for the period spanning 1992–2010. After removal of the wind-driven components from the drifter velocities and low-pass filtering in bins of 1° × 1° × 1 week, maps of surface geostrophic circulation (mean flow and kinetic energy levels) are produced using the drifter and/or satellite data. The mean currents and kinetic energy levels derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
146
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 37 publications
19
146
0
1
Order By: Relevance
“…Studies based on data including last three decades showed that seawater temperature increased approximately 1-2°C (PancucciPapadopoulou et al, 2012;Bianchi et al, 2014) and warming trend is 0.06°C/year in the south Aegean Sea Skliris et al, 2011, Shaltout andOmstedt, 2014). As it is well known, the SST gradient of whole Aegean subbasin is significantly controlled by water exchange between cold/fresh Black Sea water entering through the Dardanelles Strait and warm/saline Levantine basin water entering through the Cretan Arc Straits (Zervakis et al, 2000;Poulain et al, 2012). Besides, the Aegean SST varies zonary and seasonally, even at the same latitude, due to the Etesian winds and water currents (Kotroni et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on data including last three decades showed that seawater temperature increased approximately 1-2°C (PancucciPapadopoulou et al, 2012;Bianchi et al, 2014) and warming trend is 0.06°C/year in the south Aegean Sea Skliris et al, 2011, Shaltout andOmstedt, 2014). As it is well known, the SST gradient of whole Aegean subbasin is significantly controlled by water exchange between cold/fresh Black Sea water entering through the Dardanelles Strait and warm/saline Levantine basin water entering through the Cretan Arc Straits (Zervakis et al, 2000;Poulain et al, 2012). Besides, the Aegean SST varies zonary and seasonally, even at the same latitude, due to the Etesian winds and water currents (Kotroni et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Theocharis et al, [2002a] observed a few years after the EMT (1997-1999) a reversal of the upper layer circulation in the Central Ionian Sea which returned to the pre-EMT cyclonic pattern, while AW re-established its pre-EMT eastward flow toward the Levantine. Further studies [Borzelli et al, 2009;Gačić et al, 2010Gačić et al, , 2011Poulain et al, 2012] have confirmed that in both 1997 and 2006 the Ionian Sea upper circulation demonstrated reversals and concluded that the changes in the Ionian Sea upper layer circulation pattern is a recurrent phenomenon occurring on an almost decadal time scale. Gačić et al [2010Gačić et al [ , 2011 proposed a feedback mechanism, named the Adriatic-Ionian Bimodal Oscillating System (BiOS), between the observed North Ionian upper layer circulation inversions and the water mass redistributions in the Ionian Sea which relate to variations of the thermohaline properties of waters formed in the Southern Adriatic Sea.…”
Section: Deep Water In the Cretan Sea And The Eastern Mediterranean Tmentioning
confidence: 89%
“…Although the determination of upper wind and wave-driven currents provided by the above equation may not be accurate (see for example Rascle and Ardhuin, 2009), observations do see, in general, differences between different types of drifters (Rio et al, 2014). Interestingly, these differences are very small in the Mediterranean (Poulain et al, 2009(Poulain et al, , 2012. Although the slab model has vertically homogeneous velocities, the inclusion of the Coriolis-Stokes induces vertical variations of the velocity field since, in general d S is smaller than the mixed-layer depth (H in Eq.…”
Section: Wave Solutionmentioning
confidence: 99%
“…(20) and (23), some approaches to determine the windinduced ageostrophic contribution of the velocity field are physically based statistical models calibrated with independent observations of the velocity field, typically surface drifters (e.g., Lagerloef et al, 1999;Rio and Hernandez, 2003;Poulain et al, 2012). The most widely used model assumes…”
Section: Wind Solutionmentioning
confidence: 99%